Prevalence and Associated Factors of Delayed Diagnosis of Type 2 Diabetes Mellitus in a Tertiary Hospital: A Retrospective Cohort Study - Kotchakorn Dulyapach; Pitchayanont Ngamchaliew; Polathep Vichitkunakorn; Phoomjai Sornsenee; Kittisakdi Choomalee (Frontiers Media S.A., 2022)
Objective: To determine the prevalence and associated factors of delayed diagnosis of type 2 diabetes mellitus (DM) among outpatients in a tertiary hospital.Methods: This retrospective cohort study was conducted among outpatients aged ≥35 years with twice fasting plasma glucose (FPG) levels ≥126 mg/dl between 1 January 2018, and 31 December 2020. The prevalence and pattern of delayed diagnosis of DM were defined using the Thai Clinical Practice Guideline (CPG) for Diabetes, 2017, and the American Diabetes Association (ADA) 2017. The cut-off time for FPG level confirmation of 3 months was used to evaluate delayed diagnoses and associated factors. Multiple logistic regression was used to identify variables associated with delayed diagnoses.Results: Of 260 participants, 96.9% and 85.4% had delayed diagnoses as defined by the Thai CPG and the ADA, respectively. Factors significantly associated with delayed diagnosis were hypertension, non-cash insurance, and >10 years of physician experience.Conclusion: Undiagnosed diabetes and diagnosis delay should be a concern in tertiary settings. Senior physicians should focus on patients with higher FPG levels, particularly those who have hypertension, and use non-cash insurance schemes.